2018
DOI: 10.4172/2471-9315.1000146
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Pantoea and Kosakonia Isolated from Buckwheat Sprouts on Obese Mice

Abstract: Objective: This study aims to investigate the effects of surface bacteria of buckwheat sprouts on obesity. We examine whether these bacteria have probiotic properties. Methods: Since P-36 and P-37 strains were present in large amounts on the buckwheat sprouts surface, identification of species was carried out by intestinal bacteria identification kit and 16S rRNA gene analysis. Subsequently, to investigate the biological effects, P-36 and P-37 strains were divided into two groups, heat-treated dead bacteria an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Nonetheless, looking at the increase in research on buckwheat sprouts in various countries around the world, it seems that buckwheat sprouts are being proved highly functional for health as well as having high commercial value. Moreover, our findings have shown that not only buckwheat sprouts but also bacteria adhering to buckwheat sprouts have beneficial effects against obesity, owing to their blood-glucose suppression effect [6].…”
Section: Conclusion and Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Nonetheless, looking at the increase in research on buckwheat sprouts in various countries around the world, it seems that buckwheat sprouts are being proved highly functional for health as well as having high commercial value. Moreover, our findings have shown that not only buckwheat sprouts but also bacteria adhering to buckwheat sprouts have beneficial effects against obesity, owing to their blood-glucose suppression effect [6].…”
Section: Conclusion and Discussionmentioning
confidence: 76%
“…In the old days, they were cultivated to compensate for vegetable shortages during the winter and, by and large, they were produced/consumed locally. In recent years, however, buckwheat sprouts are attracting attention as old and new vegetables due to the growing interest in health foods and cities developing activities that promote the use of local agricultural products (slow-food movement) [6].…”
Section: Introductionmentioning
confidence: 99%
“…It is also interesting to note that MGR1 was clustered with the facultative pathogen, K. cowanii with a 61% similarity among them (Figure 2). K. cowanii is found in plants and acts as an opportunistic facultative human pathogen [31]; it is predicted to contain probiotics [32]. Furthermore, Kosakonia sp.…”
Section: Similarity and Phylogenetic Tree Analysismentioning
confidence: 99%
“…Microorganisms in environmental samples are identified by sequential screening, isolation, and culture steps, followed by verification of their physiological characteristics and morphological classification (Garland and Mills, 1991; Shi-Ying et al, 2018; Yamanouchi et al, 2018a; Dahal et al, 2018). Isolation of the unicellular protozoan, Amoeba, from soil is particularly challenging, time-consuming, labor-intensive, and requires complex culture purification techniques and significant expertise for morphological evaluation (Denet et al, 2017; Shokri et al, 2016; Yamanouchi et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%